Critical role of AMPK in redox regulation under glucose starvation - Ren, Yi; Shen, Han-Ming (Redox biology, 2019)
Glucose starvation is one of the major forms of metabolic stress in cancer cells. Deprivation of glucose impairs glycolysis and the pentose phosphate pathway, which elicits oxidative stress due to enhanced production of reactive oxygen species (ROS) and impaired antioxidant system, leading to redox imbalance and cell death. Under glucose starvation, the 5′ AMP-activated protein kinase (AMPK) plays a critical role in maintaining redox homeostasis and cell survival via multiple pathways, such as regulation of fatty acid metabolism and antioxidant response. Convergence of ROS and the glucose metabolic pathway reveals novel molecular targets for the development of effective cancer therapeutic strategies. Interestingly, AMPK, along with its upstream kinase liver kinase B1 (LKB1), has been regarded to play a tumor suppressor role. However, emerging studies have provided novel insights into the pro-tumor survival function of the LKB1-AMPK pathway. Therefore, targeting metabolic and oxidative stress in cancer cells, with manipulation of AMPK activity, is a promising strategy in developing novel cancer therapeutic agents.